Synthesis of New Cyclic Amines-Linked Metronidazole Derivatives as Possible Prodrugs - Q. Abdul-Kadir, Maadh; E. AL-Ani, Nadhum; M. Alwan, Shakir (Iraqi Journal of Pharmaceutical Sciences, 2017)
Certain cyclic amine derivatives of metronidazole via acetate spacer were prepared. Cyclic amines used are piperidine and piperazine to improve the physicochemical properties and reduce some of metronidazole side effects. This is believed to be done by modification of its structural features to get prodrugs with improved properties over that of metronidazole. The present work includes esterification of metronidazole with choroacetic acid, N-alkylation of the cyclic amines by the halogenated ester and characterization of their structures by spectral(UV and IR) and elemental(CHN)analysis.The melting points, degree of solubilities and partition coefficients were also determined. Both metronidazole-piperazine and metronidazole-piperidine derivatives have different structural and physicochemical properties that may be excellent to diminish problems associated with metronidazole.Key words: Metronidazole, chloroacetate, prodrug.